Creating, Sustaining and Realising the Value of a Faculty-wide Community of Teaching Practice - Honey, Michelle; Aspden, Trudi; Bhargava, Anuj; Carrucan-Wood, Louise; Tsai, Angela; Sim, Jenny (International Journal of Innovative Research in Medical Science, 2019)
Communities of practice are frequently described and discussed in academic literature and within education. They are depicted as groups of people with a shared interest coming together and in a higher education setting this shared interest relates to the practice of teaching and learning. The establishment of a cross-discipline faculty-wide community of practice to support educators in higher education is novel. This paper describes the establishment of a community of practice within one university faculty uniting educators across multiple disciplines within the Faculty. Data spanning thirty months since the inception of a teaching and learning community are presented. The findings illustrate a growing community of practice, along with perceived benefits and future directions. The creation of an interprofessional faculty-wide community of practice illustrates how educators can be drawn together because of their common passion for teaching and learning and a mutual concern of how to maximise student learning.